Pengembangan mata kuliah industri kimia berkelanjutan dengan metode pembelajaran berbasis masalah - Hans Kristianto; Yos Tri Atmodjo; Linda Gandajaya (JURNAL PENDIDIKAN SAINS (JPS), 2019)
In this paper we described preparation of new sustainability course that used problem based learning in its teaching learning activities. The new course was deemed necessary to prepare our future chemical engineers that could apply their knowledge in sustainability frameworks. This course is taught at 8th semester of curriculum thus it should accommodate the depth learning materials that integrate basic knowledge of chemical engineering and apply it in the context of sustainability. Problem based learning is considered appropriate to accommodate these needs. Furthermore, we measured the difference of students’ learning approach before and after participating 1 semester problem based learning session, using Study Process Questionnaires (SPQ). It was found that there was increase of deep approach with decrease of surface approach values. Positive feedbacks were also given by the students, as they could explore learning materials, team works, and other personal soft skills.